Α and β Conformational preferences in fibril forming peptides characterised using NMR and CD techniques. Issue 1 (2004) - Pertinhez Pertinhez, Thelma A. Thelma A.; Sherwood Sherwood, Amanda K. Amanda K.; Fraceto Fraceto, Leonardo F. Leonardo F.; Bouchard Bouchard, Mario Mario; Pitkeathly Pitkeathly, Maureen Maureen; Smith Smith, Lorna J. Lorna J.
Abstract : Peptide fragments taken from residues 18‒54 of short consensus repeat 3 (SCR3) from the human complement receptor CR1 have been found in aqueous solution to slowly aggregate and form fibrils. NMR studies of the monomeric form of these peptides show that they are essentially unfolded in aqueous solution and that they all have an increased helicity in TFE solutions. The behaviour of residues 28‒31 from SCR3 is particularly interesting. These residues have a high β -sheet propensity in the native protein and a seven peptide containing their sequence is found to form fibrils despite its short length. However, NMR studies show that these residues adopt a well-defined α -helix in 80% TFE and under these conditions fibril formation has not been observed. These data demonstrate the strong dependence of conformational propensities on environment.